2012
DOI: 10.1088/0004-637x/753/1/89
|View full text |Cite
|
Sign up to set email alerts
|

First Simultaneous Detection of Moving Magnetic Features in Photospheric Intensity and Magnetic Field Data

Abstract: The formation and the temporal evolution of a bipolar moving magnetic feature (MMF) was studied with high spatial and temporal resolution. The photometric properties were observed with the New Solar Telescope at Big Bear Solar Observatory using a broadband TiO filter (705.7 nm), while the magnetic field was analyzed using the spectropolarimetric data obtained by Hinode. For the first time, we observed a bipolar MMF simultaneously in intensity images and magnetic field data, and studied the details of its struc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…These brightenings have been reported in previous studies (Lim et al 2011(Lim et al , 2012Yang et al 2013). Lim et al (2011) detected a slight brightening in the TiO and Hα filtergrams.…”
Section: Summary and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These brightenings have been reported in previous studies (Lim et al 2011(Lim et al , 2012Yang et al 2013). Lim et al (2011) detected a slight brightening in the TiO and Hα filtergrams.…”
Section: Summary and Discussionsupporting
confidence: 89%
“…Yang et al (2013) also reported that the features moving with magnetic fragments were accelerated up to about 6 km s −1 prior to the occurrence of the EB. Meanwhile, some authors reported that the EGFs might be associated with the EFs and MMFs (Otsuji et al 2007;Guglielmino et al 2010;Lim et al 2011Lim et al , 2012Ortiz et al 2014). Most of these studies, however, highlighted either the connection between magnetic elements and photospheric features, or that between magnetic elements and EBs.…”
Section: Introductionmentioning
confidence: 99%
“…(2017 c ). Surprisingly, in their work there was no evidence for the sign reversal that was expected based on theoretical models (Blackman & Brandenburg 2003) and as was also seen in the active region AR 11515, which was exceptionally helical (Lim, Yurchyshyn & Goode 2012; Wang et al. 2014; Zhang et al.…”
Section: The Solar Dynamomentioning
confidence: 85%
“…The work done so far has shown that at the solar surface the magnetic helicity density is negative in the northern hemisphere and peaks at k ≈ 0.06 Mm −1 , which corresponds to a scale of approximately 100 Mm; see Brandenburg et al (2017c). Surprisingly, in their work there was no evidence for the sign reversal that was expected based on theoretical models (Blackman & Brandenburg 2003) and as was also seen in the active region AR 11515, which was exceptionally helical (Lim, Yurchyshyn & Goode 2012;Wang et al 2014;Zhang et al 2016). A positive sign of magnetic helicity has also been seen in the mean-field computations of Pipin & Pevtsov (2014).…”
Section: Magnetic Helicity Spectramentioning
confidence: 92%
“…On magnetogram time series, moving magnetic features (MMFs) are observed to originate from the outer penumbra, become isolated magnetic elements, move radially outward into the moat regions, and eventually disappear among the network fields. A series of achievements on MMFs (Harvey & Harvey 1973;Vrabec 1974;Brickhouse & Labonte 1988;Lee 1992;Zhang et al 1992Zhang et al , 2003Shine & Title 2001;Yurchyshyn et al 2001;Bernasconi et al 2002;Hagenaar & Shine 2005;Sainz Dalda & Martínez Pillet 2005;Li et al 2006Li et al , 2009Li et al , 2010Ravindra 2006;Ryutova & Hagenaar 2007;Lim et al 2012;Criscuoli et al 2012;Sainz Dalda et al 2012) are summarized as follows.…”
Section: Introductionmentioning
confidence: 99%